2004
DOI: 10.1242/jcs.01500
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella typhimuriumtranscytoses flagellin via an SPI2-mediated vesicular transport pathway

Abstract: Apical colonization of polarized epithelia by Salmonella typhimurium results in translocation of flagellin to the basolateral membrane domain, thus enabling activation of toll-like receptor 5 (TLR5)-mediated pro-inflammatory gene expression. Such flagellin transcytosis occurred without a change in epithelial permeability to 40 kDa FITC dextran, did not require bacterial motility and was independent of transepithelial movement of intact bacteria. Flagellin transcytosis was blocked at 20°C, suggesting dependence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 36 publications
3
43
0
Order By: Relevance
“…Transcytosed flagellin then triggers the production of proinflammatory cytokines via the activation of Toll-like receptor 5, thereby contributing to the intestinal inflammation known to be caused by S. typhimurium. 48 In agreement with what we report here, Lyons et al show that flagellin is incorporated in vesicles and trancytosed across the epithelium without being dependent on bacterial invasion. In addition, several bacterial species are known to interact with b1-integrin 49 and some species, such as Listeria, share some common strategies for cellular uptake.…”
Section: Discussionsupporting
confidence: 93%
“…Transcytosed flagellin then triggers the production of proinflammatory cytokines via the activation of Toll-like receptor 5, thereby contributing to the intestinal inflammation known to be caused by S. typhimurium. 48 In agreement with what we report here, Lyons et al show that flagellin is incorporated in vesicles and trancytosed across the epithelium without being dependent on bacterial invasion. In addition, several bacterial species are known to interact with b1-integrin 49 and some species, such as Listeria, share some common strategies for cellular uptake.…”
Section: Discussionsupporting
confidence: 93%
“…The translocation of flagellin into the macrophage cytosol observed by these investigators is mechanistically distinct from the cytosolic translocation of flagellin reported here since in the previous study, flagellin was localized to membrane-bound vacuoles rather then being free in the cytosol. Further, flagellin transcytosis was dependent on a third T3SS, encoded on Salmonella pathogenicity island 2 (SPI-2 T3SS), and was independent of the SPI-1 T3SS (39). Taken together, these results show that flagellin interacts with the innate immune system at multiple levels to induce proinflammatory responses during Salmonella infection.…”
Section: Discussionmentioning
confidence: 78%
“…Gewirtz and colleagues (39) showed that S. Typhimurium colonizing the apical side of epi-thelial monolayers is able to mediate flagellin transcytosis to the basolaterial aspect. The translocation of flagellin into the macrophage cytosol observed by these investigators is mechanistically distinct from the cytosolic translocation of flagellin reported here since in the previous study, flagellin was localized to membrane-bound vacuoles rather then being free in the cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…SPI-2-encoded proteins appear to play a role in the transcytosis of flagellin subunits across epithelial cells, a process that is proposed to elicit proinflammatory responses by activation of basolateral Toll-like receptor 5 (Lyons et al 2004). Studies in the bovine ileal loop model established a role for the S. Typhimurium flagella master regulator flhD in fluid secretion and neutrophil recruitment (Schmitt et al 2001).…”
Section: Molecular Mechanisms Underlying the Induction Of Enteritis Imentioning
confidence: 99%